APPLICATION OF MEDIAN-EQUATION APPROACH FOR OUTLIER DETECTION IN GEODETIC NETWORKS - Hekimoglu, Serif; Erdogan, Bahattin (UNIV FEDERAL PARANA, CENTRO POLITECNICO, 2013)
In geodetic measurements some outliers may occur sometimes in data sets, depending on different reasons. There are two main approaches to detect outliers as Tests for outliers (Baarda's and Pope's Tests) and robust methods (Danish method, Huber method etc.). These methods use the Least Squares Estimation (LSE). The outliers affect the LSE results, especially it smears the effects of the outliers on the good observations and sometimes wrong results may be obtained. To avoid these effects, a method that does not use LSE should be preferred. The median is a high breakdown point estimator and if it is applied for the outlier detection, reliable results can be obtained. In this study, a robust method which uses median with 3 sigma or 3 sigma(med) as a treshould value on median residuals that are obtained from median equations is proposed. If the a priori variance of the observations is known, the reliability of the new approch is greater than the one in the case where the a priori variance is unknown.
Keywords: Median; Median Absolute Deviation; Outlier; Median Equations; Decision Matrix; Leveling Network; Geochemistry & Geophysics; Remote Sensing